Effect of a glutathione-containing dinitrosyl iron complex on the oxidative metabolic state and crystallogenic properties of rat blood plasma: a preclinical experimental study - A. K. Martusevich; A. V. Surovegina; V. V. Kononets; A. V. Davydyuk; S. P. Peretyagin (Кубанский научный медицинский вестник, 2023)
Background: The multifaceted regulatory role of nitric oxide in biological systems predetermines the high value of studying the possibilities of the external control of the compound level in organs and tissues. There are several fundamentally different ways of exogenous modulation of nitric oxide metabolism. The most promising option is the use of pharmacological donors. Dinitrosyl iron complexes (DNIC) with various ligands hold a prominent place among such donors as they are considered as a natural deposited form of nitric oxide.Objective. To study the effect of a glutathione-containing dinitrosyl iron complex on the oxidative metabolism parameters and crystallogenic activity of rat blood.Methods. A preclinical experimental randomized study was conducted on 60 sexually mature male Wistar rats weighing about 250 g. The animals were divided into 6 groups, each consisting of 10 individuals. Group 1 included intact (without any manipulations) individuals. In group 2, the rats were administered daily intraperitoneal injections of 1 ml. of 0.9% sodium chloride solution for 10 days. The rats included in the other four groups received daily intraperitoneal injections of 1 ml of dinitrosyl iron complexes with glutathione ligands in an isotonic sodium chloride solution with different agent concentrations: 0.15 mM for group 3; 0.30 mM for group 4; 0.45 mM for group 5; 0.60 mM for group 6. The final indicator of the study was the assessment of the oxidative potential and crystallogenic properties of blood under the conditions of administering various doses of glutathione-containing dinitrosyl iron complexes. The following parameters were used to assess the activity of proand antioxidant systems: lipid peroxidation intensity; the total activity of antioxidant systems, and malondialdehyde concentration. The parameters for intrinsic crystallization assessment included serum facies structural index, crystallizability, assessment of the marginal facies zone, and the destruction degree of facies elements. The obtained data calculation was performed using the software packages MS Office 2013 (Microsoft Corporation, USA) and Statistica 10 (StatSoft, USA).Results. The research established that glutathione-containing dinitrosyl iron complexes have an antioxidant effect. Moreover, the manifestation of these properties demonstrates a nonlinear dependence on their dose, with a possible optimum lying in the range of 0.3–0.45 mM. The study also revealed a tendency towards crystallogenic properties activation induced by this agent, corresponding to concentrations of 0.3 and 0.45 mM.Conclusion. The undertaken studies indicate the presence of an antioxidant effect in glutathione-containing dinitrosyl iron complexes. The manifestation of these properties demonstrates a dependence on their dose with a possible optimum varying from 0.3 to 0.45 mM. The research has established the activating effect of glutathione-containing dinitrosyl iron complex injections on the crystallogenic potential of the blood serum of healthy rats. This effect consisted in an increase in the density and complexity of crystalline elements. What is more, the maximal manifestation of this tendency (for metabolic indicators as well) corresponded to concentrations of 0.3 and 0.45 mM.